Franchising as an innovative form of business management in Ukraine - Penchuk, Anna; Tur, Olesya (My University, 2020)
The article is devoted to the study of franchising as an innovative form of Business Management in Ukraine. Its condition, structure, and capacity are analyzed. Problems and trends in the development of franchising are identified. Measures to improve the conditions of its development in Ukraine are proposed. Стаття присвячена дослідженню франчайзингу як інноваційної форми управління бізнесом в Україні. Проаналізовано його стан, структуру та місткість. Визначено проблеми та тенденції розвитку франчайзингу. Запропоновано заходи щодо покращення умов його розвитку в Україні.
Keywords: кафедра економіки праці та менеджменту; franchising; business; management; franchisor; franchise; франчайзинг; бізнес; менеджмент; франчайзер; франчайзі